The Effect of Drug Availability And Patient Satisfaction on User Loyalty of Pharmacy Services at Rsd Dr. H. Soemarno Sosroadmodjo Tanjung Selor - Rahmansyah Rahmansyah; Mujahid Mujahid; Abdul Samad Arief; Syamsul Riyadi (Journal Development Manecos, 2026)
Hospital pharmacy services play a strategic role in ensuring therapeutic success, patient safety, and building public trust in the quality of healthcare services. Optimal drug availability and patient satisfaction are important factors assumed to influence the loyalty of pharmacy service users, especially in regional hospitals facing logistical and distribution challenges. This study aimed to analyze the effect of drug availability on patient loyalty, the effect of patient satisfaction on patient loyalty, and the simultaneous effect of both variables among pharmacy service users at RSD dr. H. Soemarno Sosroadmodjo Tanjung Selor. This study employed a quantitative approach with an explanatory survey design. Data were collected through structured questionnaires distributed to 100 patient respondents who used pharmacy services and were selected using purposive sampling. The data were analyzed using multiple linear regression. The results showed that drug availability had a positive and significant effect on patient loyalty. Patient satisfaction also has a positive and significant effect on patient loyalty. Simultaneously, both variables significantly affected patient loyalty, with a coefficient of determination of 57.4%. This means that 57.4% of patient loyalty could be explained by drug availability and patient satisfaction, while the remaining proportion was influenced by other factors outside the research model. Patient satisfaction was proven to be the most dominant factor in improving loyalty. These findings confirm that improving patient loyalty depends not only on drug availability but also on the quality of service experiences perceived by patients. Therefore, hospitals need to strengthen drug inventory management and continuously improve the quality of pharmacy services to create patient satisfaction and loyalty. Future studies are recommended to expand research locations to various hospitals and apply mixed methods approaches to obtain more comprehensive insights.